Assessment of optimal ground motion intensity measure for high-speed railway girder bridge (HRGB) based on spectral acceleration. (1st February 2022) - Hu, Zhangliang; Wei, Biao; Jiang, Lizhong; Li, Shanshan; Yu, Yujie; Xiao, Chun
Highlights: The contribution of high-order modes cannot be ignored for high-speed rail girder bridges. A new intensity measure, S*, composed of spectral acceleration and mass participation coefficient is proposed. The attenuation relationship in terms of the new intensity measure is deduced. S* is the optimal IM for high-speed rail girder bridges. Abstract: In the performance-based earthquake engineering framework, the ground motion intensity measure (IM) plays both the role of predicting structural seismic response and calculating seismic hazard curves. This study investigates the optimal ground motion IM for high-speed railway girder bridges (HRGBs). To that end, three representative HRGBs are selected for performing modal analysis first and results show that the vibration modes of HRGBs are scattered, and the contribution of high-order modes cannot be ignored. Then, a new intensity measure, S*, calculated by taking the spectral acceleration as the base and the mass participation coefficient as the index, is proposed. Through probabilistic seismic demand analysis (PSDA), compared with other 17 IMs, S* is more feasible, efficient and sufficient. Moreover, the attenuation relationship in terms of S* is proposed by simply modifying the existing attenuation models. Thus, S* is considered as the optimal IM for HRGBs.